2016
DOI: 10.1182/blood-2015-11-683334
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a comprehensive genomic diagnostic tool for myeloid malignancies

Abstract: Key Points• We develop and validate Karyogene, a comprehensive one-stop diagnostic platform for the genomic analysis of myeloid malignancies.• Karyogene simultaneously detects substitutions, insertions/deletions, translocations, copy number and zygosity changes in a single assay.The diagnosis of hematologic malignancies relies on multidisciplinary workflows involving morphology, flow cytometry, cytogenetic, and molecular genetic analyses. Advances in cancer genomics have identified numerous recurrent mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 43 publications
2
52
0
Order By: Relevance
“…In human AML, copy-neutral LOH is common for FLT3-ITD, but less so for mutant NRAS; for example, in a recent study we identified only one such LOH event among 13 RAS-mutant human AMLs. 13 Nevertheless, in keeping with our findings, studies using the Nras G12D/1 model, in combination with retroviral insertional mutagenesis, resulted in high-penetrance AML with frequent LOH for Nras-G12D when combined with overexpression of oncogenes such as Evi1. 6,39 The different incidence of LOH for mutant RAS between murine and human AML may operate through the fact that, in comparison with the acquisition of other oncogenic mutations (eg, Idh1-R132Q in our study), LOH for Nras-G12D may be more expedient in mice given the large numbers of Npm1 cA/1 /Nras G12D/1 preleukemic HSCs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In human AML, copy-neutral LOH is common for FLT3-ITD, but less so for mutant NRAS; for example, in a recent study we identified only one such LOH event among 13 RAS-mutant human AMLs. 13 Nevertheless, in keeping with our findings, studies using the Nras G12D/1 model, in combination with retroviral insertional mutagenesis, resulted in high-penetrance AML with frequent LOH for Nras-G12D when combined with overexpression of oncogenes such as Evi1. 6,39 The different incidence of LOH for mutant RAS between murine and human AML may operate through the fact that, in comparison with the acquisition of other oncogenic mutations (eg, Idh1-R132Q in our study), LOH for Nras-G12D may be more expedient in mice given the large numbers of Npm1 cA/1 /Nras G12D/1 preleukemic HSCs.…”
Section: Discussionsupporting
confidence: 88%
“…Validation of mutations was performed using MiSeq sequencing (Illumina) of amplicon libraries, as was previously described (see supplemental Methods, supplemental Figure 1, and supplemental Tables 6 and 7 for primer sequences). 12,13 Full details of analysis are provided in the supplemental Methods.…”
Section: Aml Exome Sequencing and Mutation Callingmentioning
confidence: 99%
“…20, [35][36][37] These studies have shown the range of application of NGS in the context of molecular diagnostics for hematologic malignancies; here, we add to this body of work by describing, in detail, key considerations around the integration of wet-bench, data analysis, and variant assessment approaches, which are all required for successful test implementation. A comprehensive validation approach needs to establish both test performance characteristics and test limitations.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 These panels may identify variants in genes associated with HHMs, 4,6 but tumor-only sequencing cannot differentiate between acquired and germ line variants. We hypothesized that we could identify some patients with HHMs using tumor-only NGS panels, and we determined the frequency at which this occurs.…”
Section: Introductionmentioning
confidence: 99%